2014
DOI: 10.7860/jcdr/2014/9676.4738
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Antibacterial Efficacy of Manuka Honey Against E.faecalis and E.coli – An In vitro Study

Abstract: Aim: To compare the antibacterial efficacy of Manuka honey against E.faecalis and E.coli. Materials and Methods: Escherichia coli (ATCC-25922) andEnterococcus faecalis (ATCC-29212) were separately inoculated in the nutrient broth and incubated at 37 o C for 24-48 hrs. Bacterial samples were kept in contact with each disinfectant solution for varying intervals of time. Once the test time had elapsed 10μL of the bacterial dilutions were plated on MuellerHinton agar and incubated for 24-48 hrs at 37°C to estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Although no study has report bacterial resistance to honey, Gram-positive isolates of Bacillus cereus and S. aureus exhibited increased in vitro sensitivity to Sidr honey (33% w/v), evidenced by the large zone of inhibition (36 mm and 34 mm, respectively) compared to E.coli and Salmonella enteritidis (27 mm and 23 mm, respectively) [31]. This is in line with previous reports where the inhibition of Gram-positive bacteria (Enterococcus faecalis and S. aureus) at lower the concentration of Manuka honey was observed while its absent/limited effect on Gram-negative bacteria (P. aeruginosa and E. coli) [32].…”
Section: Saudi Honeysupporting
confidence: 92%
“…Although no study has report bacterial resistance to honey, Gram-positive isolates of Bacillus cereus and S. aureus exhibited increased in vitro sensitivity to Sidr honey (33% w/v), evidenced by the large zone of inhibition (36 mm and 34 mm, respectively) compared to E.coli and Salmonella enteritidis (27 mm and 23 mm, respectively) [31]. This is in line with previous reports where the inhibition of Gram-positive bacteria (Enterococcus faecalis and S. aureus) at lower the concentration of Manuka honey was observed while its absent/limited effect on Gram-negative bacteria (P. aeruginosa and E. coli) [32].…”
Section: Saudi Honeysupporting
confidence: 92%
“…In a study carried out, the researchers compared the antibacterial effect of Manuka honey against Enterococcus faecalis and E. coli, a Gram-positive and a Gram-negative bacterium. The results from this study indicated that Gram-negative bacteria might be more resistant when exposed to Manuka honey [35].…”
Section: Honey's Use In Alternative Therapymentioning
confidence: 63%
“…This high content also confers a high antioxidant and antibacterial capacity, which allows it to be considered a medicinal honey. This has led to the use of Manuka honey as a reference for the comparison of bioactive compounds with others of a distinct botanical and geographical origin [ 54 , 87 , 92 , 95 , 105 , 106 , 107 ]. Regarding the comparison of the content of phenolic compounds of Manuka honey with others, such as Polish honeys, no significant differences were found ( p ≤ 0.05) in the TPC of buckwheat honey (211.0 ± 11.4 mg GAE/100 g) and honeydew (201.0 ± 9.9 mg GAE/100 g), compared to the values of the commercial Manuka honey.…”
Section: Phenolic Compounds As Indicators Of the Botanical Origin Of Honeymentioning
confidence: 99%